Estudio bibliométrico de la biblioteca de la Real Sociedad Económica Extremeña de amigos del país. Parte II. Colección del siglo XIX - Pulgarín Guerrero, Antonio; Marroquín Martínez, Laura; Herrera Morillas, José Luís (Revista General de Información y Documentación, 2009)
The aim of this paper is to study and to report globally on the stock of antiquarian books at the Library of the “Real Sociedad Económica Extremeña de Amigos del País” (Royal Extremaduran Economic Society of Friends of the Country). A recopilation of bibliographic data on this stock corresponding to the 19th centuries has been made. The results are analysed and interpreted to reflect and highlight the role played by Economic Societies of the Country. The stock studied is 5512 books from the 19th century. The evolution of the number of books is analysed, together with the productivity of the authors, place of edition, distribution of books by printer, and distribution by subject.
Keywords: Bibliometric study; “Real Sociedad Económica Extremeña de Amigos del País”; Antiquarian books; 19th centurie